Feeding a definite concentration of eicosapentaenoic and docosahexaenoic fatty acids to laying hens - NASSEF, E. E.; BAKR, A. A.; SALAMA, A. S. (Journal of the Hellenic Veterinary Medical Society, 2019)
The experiment designed to study the influences of nutritional eicosapentaenoic (EPA) and docosahexaenoic (DHA) fatty acids (FA) on performance, egg yolk fat characteristics and FA profile in laying hens. From 30 to 36 weeks of age, 180 laying hens were allotted randomly to 2 dietary treatments, each of 6 replicates (15 birds for each replicate). The control diet was supplied with soy oil while the experimental diet was supplied with EPA and DHA to create 2 different ratio of n-6 to n-3 FA (18.8:1 and 5:1, respectively). The egg production % was recorded daily. The eggs were weighed to estimate egg mass. Also, feed consumption was recorded daily and the feed conversion ratio (FCR) was estimated. The FA profile of egg yolk was determined in the last week of the experiment. The dietary EPA and DHA resulted in significantly higher egg production (76.89 versus 67.23%), weightier egg mass (42.46 versus 37. 72 g) and lower FCR (2.49 versus 2.72) than the control. Also, supplying the dietary EPA and DHA was reflected in increasing of total polyunsaturated and n-3 FA in the eggs. Moreover, reducing the ratio of n-6 to n-3 FA to 5:1 decreased egg triglycerides, total cholesterol and cholesterol associated with low density lipoprotein and very low density lipoprotein. In conclusion, supplying EPA and DHA in the diet of laying hens positively influences performance, egg yolk FA profile and cholesterol. Practically, EPA and DHA could be used in laying hen diets to improve their performance and enhance public health of egg consumers.